Commentary by Onder Ozkalipci:: Ethical criteria when a (potential) perpetrator asks a human rights organization to defend their case based on the forensic documentation of alleged torture. How shall we proceed? - Ozkalipci, Onder (Torture Journal, 2020)
I congratulate the author for bringing this topic regarding the ethical dilemmas faced by NGOs when a perpetrator of torture requests a clinical evaluation to prove claims of persecution or being victim of torture. Such dilemmas may arise in the case of NGOs whose primary mission is to provide supportive documentation for asylum claims by victims of torture, in accordance with the Istanbul Protocol. Questions related to these dilemmas may emerge in the daily practice of any rehabilitation centre for survivors of torture (RCTs). I will proceed to discuss the paper from the perspective of RCTs....